(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article describes the psychological essence of scientific and creative activity, the term scientific and creative activity, social factors influencing the development of creative qualities, student activity, ways and forms of forming critical, creative thinking in young students, the flexibility of creative thinking, and the criteria of scientific and creative activity.